Staging faith : religion and African American theater from the Harlem renaissance to World War II - Prentiss, Craig R. (New York University Press, 2013)
In the years between the Harlem Renaissance and World War II, African American playwrights gave birth to a vital Black theater movement in the U.S. It was a movement overwhelmingly concerned with the role of religion in Black identity. In a time of profound social transformation fueled by a massive migration from the rural south to the urban-industrial centers of the north, scripts penned by dozens of Black playwrights reflected cultural tensions, often rooted in class, that revealed competing conceptions of religion's role in the formation of racial identity.